2003
DOI: 10.1177/002199803029733
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Analysis of the Buckling Behavior of Composites with Delamination

Abstract: In this paper, we provide an insight into the governing mechanism of the uni-axial compressive bucklingof a delaminated composite. We propose an approximate method to analyze the bucklingbehavior as the first step to further investigate the effect of contact zone at the ends of a delamination. The agreement of the analytical results with experiments in critical values of relative axial displacement verifies our model and approach. The proposed method provides a simple and effective way to calculate the forces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…An analytical model by Shan & Pelegri [3] accounted for forces and moments at the delamination tips when the local buckling of the sub-laminate interacted with global buckling of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…An analytical model by Shan & Pelegri [3] accounted for forces and moments at the delamination tips when the local buckling of the sub-laminate interacted with global buckling of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Such investigation studies have been carried out for example by Nowoświat [32], and they involved the control and stability of Duffing oscillator. Perturbation methods have been applied to investigate the buckling of springy beams [33]. Very interesting modifications of this method and the explanation of perturbation numbers have been proposed by Skrzypczyk [34].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of a single delamination [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and multiple delaminations [17][18][19] has been investigated. Experimental [2,6,11,17,19] and theoretical studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]18] can be found. Theoretical work follows two different approaches: balance equations of linear and angular momentum [1,[4][5][6][11][12][13] or the minimum of total potential energy principle [2,3,…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [2,6,11,17,19] and theoretical studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]18] can be found. Theoretical work follows two different approaches: balance equations of linear and angular momentum [1,[4][5][6][11][12][13] or the minimum of total potential energy principle [2,3,7,8,10]. Results obtained are often validated using the finite element method (FEM) [3,7,8,10,13].…”
Section: Introductionmentioning
confidence: 99%